Pengaruh Variasi Volume Campuran Lumpur IPAL Sewon Terhadap Kuat Tekanan Batu B ata Produksi Desa Turi, Sumberagung, Sleman - Wahyu Handoyo Putro; Bambang Suwerda; Sigid Sudaryanto (Poltekkes Kemenkes Yogyakarta, 2012)
The Waste Water Treatment Plant (WWTP) at Sewon Bantul, produces sludge as the by-product. The sludge is usually dried in the sludge drying bed and only a small part of it is used as fertilizer. Each year the sludge can be yielded as much as 3300 m3 and may have negative impact i.e. supporting the existence of disease insect vector and other annoying animals. One effort for utilizing the sludge is use it as a mixture of red brick production. The aim of the study was to know the influence of the mixture variations between sludge and clay, i.e.3:1, 2:2, 1:3 and 0:4, on the pressure strength of the bricks by conducting an experiment using post-test with control group design. As the brick control were those made in Turi Village. From each mixture variationand control, 10 bricks were measured for their pressure strength in the construction laboratory.Descriptively, the control bricks had the highest pressure strength, meanwhile among the treatment groups, bricks made from mixture ratio of 3:1 were the highest but had 16,9 % reduction compared with the controls. The results of analysis by using independent t-test at 95 % significance level, showed that the pressure strength among bricks of four mixture variations were significantly different. However, the bigger the sludge was added the lower the pressure strength will be gained. Since the highest strength among the sludged bricks had not yet fulfilled the standard issued by SII-0021-78 i.e. 25 kg/cm2 , it is recommended that the bricks made of waste water sludge not to be used for heavy or high pressure building or dwelling construction.